Recession of the Rule of Law and Decline of Development in Nigeria - Jayeoba, Ayodeji (ABUAD Law Journal, 2019)
Development is generally conceived in such narrow terms that its very essence is misrepresented. More often than not development has been reduced to no more than economic development and expectedly, factors affecting development have also been restrictively conceived. This paper attempts to show that there is a direct linkage between the rule of law and development by analyzing how the presence or absence of the elements and components of the rule of law facilitates or impedes development respectively in Nigeria. The methodology adopted for the study is both doctrinal and analytical. The paper concludes that decline of rule of law in Nigeria is one of the major causes of her underdevelopment.